Cyber Crime in the Era Industrial 4.0: Analysis OTP Fraud in Hadith Perspective - Almunadi Almunadi; Titik Kurniawati; Ahmad Rofi’i; Dafis Heriansyah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This research was conducted to examine cases of OTP fraud in the view of hadith. The results and discussion of this study indicate the existence of certain hadith that prohibit committing acts of fraud including OTP fraud. This study concludes that OTP fraud is an act of criminality by deceiving its target by pretending to be a staff of a certain institution to convince its target to provide an OTP code. This is prohibited in the Qur'an and hadith so it is recommended to do tabayyun when receiving information. This research recommends that technology users be careful and not give arbitrary codes containing confidential personal data to others.